THe geospatial future of buried services responding to the requirements of the Traffic Management Act : delegate information, Wednesday 20 September 2006. (Thomas Telford, 2006)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a one-day conference held in Manchester 20 September 2006.